Balance this equation with steps C2H6 + O2 → CO2 + H2O

Given

C2H6 + O2 —-> CO2 + H2O

Balance C atoms

C2H6 + O2 —-> 2CO2 + H2O

Balance H atoms

C2H6 + O2 —-> 2CO2 + 3H2O

Balance O atoms

C2H6 + 7/2 O2 —-> 2CO2 + 3H2O

Now,

Multiply the above equation with 2 to get whole number coefficients.

2C2H6 + 7O2 ——> 4CO2 + 6H2O

Hence,

The balanced equation is 2C2H6 + 7O2 —–> 4CO2 + 6H2O

Was this answer helpful?

  
   

0 (0)

Upvote (0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question